Environmental screening for microorganisms of patient’s surrounding as the possible source of nosocomial infections in a hospital in Nepal - Pant, Narayan Dutt; Sharma, Manisha (Journal of Biomedical Sciences, 2016)
No Abstract Available. J. Biomed. Sci. 2015, 2(3):21-23.